Biochemical Characterization of Halotolerant Bacillus safensis PM22 and Its Potential to Enhance Growth of Maize under Salinity Stress - Muhammad Atif Azeem (17542080) (2022)
Salinity stress is one of the primary abiotic stresses limiting crop growth and yield. Plants respond to salinity stress with several morphophysiological, molecular, and biochemical mechanisms, however, these mechanisms need to be improved further to cope with salt stress effectively. In this regard, the use of plant growth-promoting (PGP) and halotolerant bacteria is thought to be very efficient for enhancing growth and salinity tolerance in plants. The current study aims to assess Bacillus safensis PM22 for its ability to promote plant growth and resistance to salt. The PM22 produced substantial amounts of exopolysaccharides, indole-3-acetic acid, siderophore, and 1-aminocyclopropane-1-carboxylic acid deaminase (ACC-deaminase) under saline conditions. Additionally, inoculation of the halotolerant bacteria PM22 reduced the severity of salinity stress in plants and increased root and shoot length at various salt concentrations (0, 180, 240, and 300 mM). Furthermore, PM22-inoculated plants showed markedly enhanced photosynthetic pigment, carotenoid, leaf relative water content, 2,2-diphenyl-1-picrylhydrazyl (DPPH) activity, salt tolerance index, total soluble sugar, total protein, and ascorbic acid contents compared to non-inoculated control maize plants. PM22 substantially increased antioxidant (enzymatic and non-enzymatic) activities in maize plants, including ascorbate peroxidase, peroxidase, superoxide dismutase, catalase, total flavonoid, and phenol levels. Maize plants inoculated with PM22 also exhibited a significant reduction in electrolyte leakage, hydrogen peroxide, malondialdehyde, glycine betaine, and proline contents compared to non-inoculated control plants. These physiological appearances were further validated by quantitative reverse transcription-polymerase chain reaction (qRT-PCR), which revealed the upregulation of expression in genes responsible for stress tolerance. In the current investigation, Bacillus safensis PM22 showed plant growth-promoting and salt tolerance attributes and can be utilized as a bio-inoculant to improve yield in salt stress affected areas. Other Information Published in: Plants License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/plants11131721 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.